2019
DOI: 10.3390/molecules24244552
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nano-SiOx/Chitosan Complex Coating on the Physicochemical Characteristics and Preservation Performance of Green Tomato

Abstract: A novel nano-silicon oxides (SiOx)/chitosan complex film was prepared using ultrasonic assistant in the process of dissolving chitosan and silicon oxides (SiOx), and characterized by transmission electron microscopy. Its effect on quality preservation of tomatoes (Solanum lycopersicum L. cv. Zheza 205) was investigated under ambient temperature. The results revealed that the nano-SiOx/chitosan complex (NSCC) film retarded weight loss and softness, delayed the titratable acids and total soluble solids loss, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
40
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 58 publications
8
40
0
1
Order By: Relevance
“…It seems that the application of Cs-Phe NPs could increase fruit tolerances to chilling injury by inducing the defense responses which could reduce ROS and preserving the cell membrane via the formation of phenolic and antioxidant compounds [40]. Zhu et al [41] showed that fruit coating using edible polymer such as chitosan has improved inhibition of ROS production and prevented chilling damage in fruit, which is in agreement with our findings. Some recent studies reported that coating with Cs prevented the increasing of chilling injury in fruit.…”
Section: Fruit Chilling Indexsupporting
confidence: 91%
See 2 more Smart Citations
“…It seems that the application of Cs-Phe NPs could increase fruit tolerances to chilling injury by inducing the defense responses which could reduce ROS and preserving the cell membrane via the formation of phenolic and antioxidant compounds [40]. Zhu et al [41] showed that fruit coating using edible polymer such as chitosan has improved inhibition of ROS production and prevented chilling damage in fruit, which is in agreement with our findings. Some recent studies reported that coating with Cs prevented the increasing of chilling injury in fruit.…”
Section: Fruit Chilling Indexsupporting
confidence: 91%
“…Chitosan provides uniform and stiff binding to surfaces of persimmon fruits that prevents increased respiration and delays transpiration rates [44]. Some recent studies reported that fruit coated with Cs were prevented from reducing in weight, water vapor transmission rate and O 2 /CO 2 by increasing surface and interface roughness and due to a smaller pore size, thus preventing the percentage of weight loss [41]. Menna et al [25] reported Cu-chitosan nano significantly prevented weight loss in tomato during 21 days storage, which is in accordance with our study.…”
Section: Weight Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…POD activity in the coated groups is significantly lower than in the control at 6–15 days, suggesting that the KGM/SA composite coating provide a more suitable environment for gingers storage and inhibited oxidation of phenolics (Zhu et al, 2019a). Similar changes of POD activity affected by coating were found in Pholiota nameko mushroom coated with sodium alginate‐based composite coating (Zhu et al, 2019a,b), and by sodium chloride treatment for fresh‐cut gingers preservation were found from Jia (2019).…”
Section: Resultssupporting
confidence: 62%
“…Fruits and vegetables may soften and change in texture caused via cell wall degradation during storage (Zhu et al, 2019b). Cellulase can degrade both cellulose and the b‐1,4‐glucan backbone of xyloglucan in cell wall, and thus is related to qualities of the fruits and vegetables (Zhou, Li, Yan, & Xie, 2011).…”
Section: Resultsmentioning
confidence: 99%